Implementasi Pembelajaran Al-Qu’ran terhadap Perkembangan Nilai Agama dan Moral Anak Usia Dini - Nur Asrima Pasaribu (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to implement learning the Koran on the development of religious and moral values in early childhood at RAQ HAJJAH HALIMATUN, using data collection methods, which include: observation, interviews, and documentation. And the results obtained by this study are that children can get to know the religion of Islam, children can know the names of surahs, children have also memorized daily prayers that are usually done, and children can also know how to be polite, respect those who are more aged, and also can adapt to the surrounding environment.